World Development Indicators 2004 - World Bank (World Development Indicators, 2004)
World Development Indicators, the World Bank's respected statistical publication presents the most current and accurate information on global development on both a national level and aggregated globally. This information allows readers to monitor the progress made toward meeting the goals endorsed by the United Nations and its member countries, the World Bank, and a host of partner organizations in September 2001 in their Millennium Development Goals. The 400-page print edition of World Development Indicators 2004 allows you to consult over 80 tables and over 800 indicators for 152 economies and 14 country groups, as well as basic indicators for a further 55 economies. There are key indicators for the latest year available, important regional data, and income group analysis. The report contains six thematic presentations of analytical commentary covering: World View, People, Environment, Economy, States and Markets, and Global Links. The CD-ROM editions contain 40 years of time series data for more than 200 countries from 1960-2002, single-year observations, and spreadsheets on many topics. It contains more than 1,000 country tables and the text from the World Development Indicators 2004 print edition and the World Bank Atlas 2003. The Windows® based format permits users to search for and retrieve data in spreadsheet form, create maps and charts, and fully download them into other popular software programs for study or presentation purposes